Is WhatsApp free of the elites : the 2018 General Elections in Malaysia - Kevin Fernandez,; Marwan Ismail,; Ravindaran Maraya, (Penerbit Universiti Kebangsaan Malaysia, 2021)
2018 was a particularly significant year for Malaysia, as citizens democratically dethroned a 61-year-old regime, Barisan Nasional (BN, the National Front), and replaced it with Pakatan Harapan (PH, the Alliance of Hope) without bloodshed. This article attempts to systematically analyze the evolution of new media from the 2008 election (taking place in the blogging era, which contributed to the “electoral tsunami” in Malaysia that year) to 2018, which saw the rise of encrypted messaging services such as WhatsApp, a formidable point for the dissemination and consumption of political news in Malaysia. Methodologically, the normative method of the shared values theory was adopted to better explain how new media is currently used to shape the political ideas of ordinary Malaysians. The findings suggest that there is a clear attempt by political leaders to coopt opinion leaders at various levels, particularly religious leaders, academicians, think tanks and non-governmental organizations (NGOs), with the intention of influencing and shaping the political leanings of those who are less interested in politics, using a centralized agenda-setting mechanism. The findings also suggest that opinion leaders were purposely selected according to their higher social capital value and social authority, and evidence from the study suggests that instant messaging services are not totally free from the influence of political and economic elites.